Does gender matter for firm performance? : evidence from Eastern Europe and Central Asia - Sabarwal, Shwetlana (Policy research working paper, 2008)
"Using 2005 firm level data for 26 countries in Eastern and Central Europe, this paper estimates performance gaps between male and female-owned businesses, while controlling for location by industry and country. The findings show that female entrepreneurs have a significantly smaller scale of operations (as measured by sales revenues) and are less efficient in terms of total factor productivity, although the difference is small. However, women entrepreneurs generate the same amount of profit per unit of revenue as men. Although both male and female entrepreneurs in the region are sub-optimally small, women's returns to scale are significantly larger than men's, implying that women would gain more from increasing their scale. The authors argue that the main reasons for the sub-optimal size of female-owned firms are that they are both capital constrained and concentrated in industries with small firms. "--World Bank web site